Fetal nutrition and adult disease [ programming of chronic disease through fetal exposure to undernutrition - Langley-Evans, S. C. (Frontiers in nutritional science, 2004)
"This book, which brings together the perspectives of leading researchers from Europe, the USA and Australasia, provides the reader with a detailed account of the evidence for and against the nutritional programming of human disease, and considers the biological basis of programming. The book addresses a topic of great current interest and consists of three sections: programming the fetus; programming human disease; and the biological basis of nutritional programming. The book has been written for advanced students and researchers in human nutrition."--Jacket.